Clinical audit for the diagnosis of Celiac disease - Zúñiga Montero, Marco Antonio (2014)
Celiac disease is a chronic inflammation of the small intestine’s mucose due to gluten intolerance. Not long ago, it had been considered an unfrequent disease, but the increase of clinical suspicion and the coming of new serological tests have made it easier to diagnose and increase detected cases. Therefore, nowadays, it is known as a high frequency condition. However, in Costa Rica, there is not any protocol for physicians to carry out their diagnosis, and that is the purpose of this research: to analyze the way physicians in Costa Rica manage their patients with celiac disease, and subsequently, to come up with a proposal in accordance with the recommendations provided by The Guía de PrácticaClínica and the best scientific evidence. In order to accomplish this, physicians will be subjects of structured interviews, clinical practice guidelines and scientific studies to handle celiac disease will be analyzed, gathered information will be compared to scientific evidence, and finally the proposal based on recommendations from The Guía de PrácticaClínica and scientific studies will be worked out. The impact will be to provide scientific strictness when drawing up the diagnosis of celiac disease, which entails providing safe, timely and quality based healthcare.